The Motives For Joining The University With a Sample Of Damascus University Students Faculty Of Education and College Of Civil Engineering (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aims to uncover the motives for university enrollment for a sample of Damascus University students Faculty of Education and College of Civil Engineering, and to detect the differences between the averages of the students' scores according to the university enrollment motivation, the gender variables and the academic specialization.                                 Tools were used to measure the motivation of university enrollment by the researcher.    The most important findings of the research:There was a high level of motivation for university enrollment among the students in the research sample.The high level of motivation to enroll in the university included social motives, cognitive motives, psychological motives, professional motives and academic motives.        The existence of statistically significant differences between males and females on the total score of the motives of university enrollment in both the psychological motives and cognitive motives and professional motives for females, and the absence of statistically significant differences between males and females in academic motive and social motives.  The existence of statistically significant differences between the students of the Faculty of Education and the students of the Faculty of Civil Engineering on the total score of the motives of the university enrollment in both the psychological motives and the cognitive motives and the social motives for the benefit of the students of the Faculty of Education and the absence of statistically significant differences between the students of the Faculty of Education and students of the Faculty of Civil Engineering in academic motives  and professional motivation.
Keywords: motivation; motivation to join the university, Damascus University.